2019
DOI: 10.1128/mra.01292-18
|View full text |Cite
|
Sign up to set email alerts
|

Proposed New Strain of Canine Kobuvirus from Fecal Samples of Brazilian Domestic Dogs

Abstract: A proposed new strain of canine Kobuvirus was identified in fecal samples of domestic dogs from a rural community located in the municipality of Peixe-Boi, Pará, Brazil. The nucleotide identity was 92.3% similar to other representatives of the family Picornaviridae, genus Kobuvirus, and species Aichivirus A, which suggests that this is possibly a new strain within this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Aichivirus A is divided in six types: human Aichi virus (AiV) (Yamashita et al 1991), canine kobuvirus (Kapoor et al 2011;Barros et al 2019), murine kobuvirus (Phan et al 2011), Kathmandu sewage kobuvirus (Ng et al 2012), roller kobuvirus (Pankovics et al 2014) and feline kobuvirus (Chung et al 2013). The other species also display a certain degree of variability, 3 types having been described in Aichivirus B, and 2 types in the species Aichivirus C, Aichivirus D and Aichivirus F. Finally, three genotypes (Fig.…”
Section: History and Taxonomymentioning
confidence: 99%
“…Aichivirus A is divided in six types: human Aichi virus (AiV) (Yamashita et al 1991), canine kobuvirus (Kapoor et al 2011;Barros et al 2019), murine kobuvirus (Phan et al 2011), Kathmandu sewage kobuvirus (Ng et al 2012), roller kobuvirus (Pankovics et al 2014) and feline kobuvirus (Chung et al 2013). The other species also display a certain degree of variability, 3 types having been described in Aichivirus B, and 2 types in the species Aichivirus C, Aichivirus D and Aichivirus F. Finally, three genotypes (Fig.…”
Section: History and Taxonomymentioning
confidence: 99%
“…In Brazil, CaKV was detected in multiple tissues of a puppy with clinical signs of gastroenteritis resulting in the first reported occurrence of extraintestinal CaKV in dogs [21]. The occurrence of other kobuviruses species have been reported in diarrheic fecal samples from pig and cattle in Brazil [19,20], and there is only one study reporting a strain of CaKV found in fecal samples of nondiarrheic dogs in the country [2].…”
Section: Introductionmentioning
confidence: 99%
“…Canine enteric coronavirus and canine distemper virus, as well as other low-prevalence agents (such as bocavirus, astrovirus, and kobuvirus), have been detected in dogs with enteric diseases worldwide (BARROS et al, 2019;BODEWES et al, 2014;CHOI et al, 2014;DOWGIER et al, 2017;LI et al, 2011). Although, we have not observed characteristic/pathognomonic intestinal lesions associated with these agents, we cannot completely rule out their involvement in some cases.…”
Section: Discussionmentioning
confidence: 62%